(3GdEJLGgGJ GdMOjKI aj GbJUGOjGJ GdEOGQI (B:s (3eONd Gdi GdCdajI GdKGdKI (B/s - (3GddjKj, eMeO Ydis; (3Sjajf, dWaj dhjRs ((3GdbGgQI(B: s (3GdOGQ GdLGeYjI ddfTQ(B, s, 2005)
(3GdWdH hGdYQV hGdJhGRf(B- (3GdEfJGL hGdJcGdja(B- (3gjcd GdShb hGdJSYjQ(B- (3GdeeGQGSGJ GdSYQjI(B- (3GdJMdjd GdbQGQj(B- (3Jbhje GdESJKeGQ(B- (3feGPL Gdfbd hGdJhRjY(B- (3eSCdI GdJNRjf aj GdEbJUGO GdEOGQj(B- (3GSJNOGe fXQjI GdeHGQjGJ aj EbJUGOjGJ GdEOGQI(B- (3GdHQeLI GdNWjI hEbJUGOjGJ GdEOGQI(B- (3EOGQI GdeTQhYGJ(B- (3EOGQI GdLhOI GdTGedI hEbJUGOjGJ GdEOGQI(B.s
Keywords: (3EbJUGOjGJ GdEOGQI(B- (3GdCdajI GdKGdKIs